AVALIAÇÃO DA ECOTOXICIDADE DE MERCÚRIO EM TRÊS TIPOS DE SOLOS UTILIZANDO ENSAIOS ECOTOXICOLÓGICOS COM OLIGOQUETAS - Cesar, Ricardo; Colonese, Juan; Silva, Marianna; Bertolino, Luiz Carlos; Castilhos, Zuleica; Egler, Silvia; Polivanov, Helena; Bidone, Edison; Perez, Daniel (Geochimica Brasiliensis, 2012)